Diferensiasi Pengajaran Tari pada Usia 4-9 Tahun di Sanggar Tari Sobokartti Semarang - Nurul Hikmah; Rimasari Pramesti Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was motivated by the importance of dance in fostering aesthetic sensitivity, discipline, and cultural character in the younger generation. However, dance teaching practices in Indonesia are generally uniform and do not take into account the age and developmental stages of students, resulting in suboptimal learning outcomes. Several previous studies (Budiman et al., 2022; Da Ary & Markamah, 2024; Yuliyanti & Budiman, 2023) have shown the weaknesses of dance teaching methods that do not adapt to the characteristics of the participants, resulting in low mastery of techniques, motivation, and understanding of cultural values. Based on these issues, this study aims to examine the application of content, process, and product differentiation in dance learning at the Sobokartti Dance Studio in Semarang, which trains participants aged 4 to 25 years. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The results of the study show the application of teaching that is tailored to age characteristics, ranging from imitative movements in children to reflection on cultural values in adults. These findings prove that differentiated teaching methods are effective in improving the relevance and quality of traditional dance learning. The implication is that this model can be used as a reference for non-formal educational institutions in developing adaptive arts learning that is oriented towards the preservation of local culture.